Survey Paper on Performance Evaluation of 4G and 5G System using Space Time Block Coding Technique - Panthi, Dolly; Jatav, Munna Lal (International Journal of Computer Sciences and Engineering, 2019)
In this paper, the review of the multiple input multiple output using space time block code on IEEE 802.16 system. The Worldwide Interoperability for Microwaves Access technology which can offer high speed voice, image, and video and data service up to base on standard 802-16 wireless MAN is configured in the same way as a traditional cellular network. The range of WiMAX makes the system very attractive for users, but there will be slightly higher BER at low SNR. In this paper the study of different types of 4G and 5G technique and explain the advantage and disadvantage of the system.